2016
DOI: 10.1017/s0033291716000581
|View full text |Cite
|
Sign up to set email alerts
|

The set-shifting profiles of anorexia nervosa and autism spectrum disorder using the Wisconsin Card Sorting Test: a systematic review and meta-analysis

Abstract: Difficulties in set-shifting are commonly reported in both autism spectrum disorder (ASD) and anorexia nervosa (AN) populations. Despite this, it is not known whether this cognitive profile persists across different ages, or whether the profiles seen in ASD and AN are comparable. This systematic review and meta-analyses aimed to compare the set-shifting profiles, as measured by the Wisconsin Card Sorting Test (WCST) in adults and younger people with either ASD or AN, relative to healthy controls (HCs) and to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
134
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 109 publications
15
134
4
3
Order By: Relevance
“…The findings of this study suggesting that there are in fact no differences in the perception of sweetness or fat intensity between people with AN and HC indicates that the documented aversion to this stimuli in individuals with AN reflects subjective perception, rather than objective taste alterations. Instead, sweetness and fat avoidance in AN may instead be driven by the cognitive resistance and inflexibility documented in this population (Lang, Stahl, Espie, Treasure, & Tchanturia, 2014; Tchanturia et al, 2012; Westwood, Stahl, Mandy, & Tchanturia, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study suggesting that there are in fact no differences in the perception of sweetness or fat intensity between people with AN and HC indicates that the documented aversion to this stimuli in individuals with AN reflects subjective perception, rather than objective taste alterations. Instead, sweetness and fat avoidance in AN may instead be driven by the cognitive resistance and inflexibility documented in this population (Lang, Stahl, Espie, Treasure, & Tchanturia, 2014; Tchanturia et al, 2012; Westwood, Stahl, Mandy, & Tchanturia, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Current evidence points to a strong role for three particular deficits, impaired theory of mind (Caglar-Nazali et al, 2014;Davis et al, 2016 ), weak central coherence (Lang et al, 2014), and deficits in executive functions, including problems in set-shifting (Roberts et al, 2007;Tchanturia et al, 2012;Westwood et al, 2016). Social interaction impairments and reciprocal communication deficits, which are key symptoms of ASD, have also been reported in ED patients (Wentz et al, 2009;Zucker et al, 2007).…”
Section: Autistic Traits In Clinical Eating Disordersmentioning
confidence: 99%
“…impaired set-shifting and theory of mind as well as weak central coherence) (e.g. CaglarNazali et al, 2014;Westwood et al, 2016, Zucker et al, 2007, investigations into other mechanisms linking the two disorders, have been scarce. Given that deficits in emotion regulation have been found in both EDs (Meyer et al, 2010;Svaldi et al, 2012) and ASD populations (Globerson et al, 2015), it is possible that the relationship between these disorders may be mediated by emotion-related traits.…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms were assessed in all patients using the Beck Depression Inventory (BDI). The Regional Ethical Review Board at the University of Gothenburg approved the study (registration number [7][8][9][10][11][12][13][14], and all participants gave written informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…4 For instance, affected women typically exhibit perfectionism, particularly regarding symmetry and exactness, 5 obsessive-compulsiveness, low cooperativeness, low novelty-seeking, impaired social cognition 6,7 and set-shifting difficulties. 8 Moreover, a large number of studies have found persistently elevated levels of autistic traits in patients with anorexia nervosa, 4,7,[9][10][11][12][13] and autistic traits and eating disorder behaviours are correlated in typically developing children. 14 In fact, a relatively high proportion of women with anorexia nervosa also meet the criteria for ASD, 11,15 and the prevalence of ASD is higher in populations affected by eating disorders.…”
Section: Introductionmentioning
confidence: 99%